2021
DOI: 10.29040/jap.v21i02.1513
|View full text |Cite
|
Sign up to set email alerts
|

Model Kepatuhan Wajib Pajak (Studi pada Wajib Pajak yang Melakukan Usaha di Kota Medan)

Abstract: This study aims to produce a Taxpayer Compliance model (Study on Taxpayers Doing Business in Medan City. The research was conducted in Medan City. The population of this study is taxpayers who carry out business activities in Medan City, both individual taxpayers and businessmen. corporate tax. Because the number of taxpayers who carry out activities in Medan City is very large and the population is unknown, a sample selection was made and 97 taxpayers were obtained. The sample selection was taken by convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Taxpayer compliance can be measured by understanding all provisions of tax laws and regulations, such as filling out forms completely and clearly, calculating the amount of tax payable correctly, paying and reporting tax payable on time. In taxation, we can give an understanding that tax compliance is obedience, submission, and compliance with and implementing tax provisions (Dahrani et al, 2021). Based on the above understanding, it can be concluded that taxpayer compliance is an attitude of a taxpayer's sense of responsibility and awareness as a citizen to always fulfill his tax obligations.…”
Section: Taxpayer Compliancementioning
confidence: 98%
“…Taxpayer compliance can be measured by understanding all provisions of tax laws and regulations, such as filling out forms completely and clearly, calculating the amount of tax payable correctly, paying and reporting tax payable on time. In taxation, we can give an understanding that tax compliance is obedience, submission, and compliance with and implementing tax provisions (Dahrani et al, 2021). Based on the above understanding, it can be concluded that taxpayer compliance is an attitude of a taxpayer's sense of responsibility and awareness as a citizen to always fulfill his tax obligations.…”
Section: Taxpayer Compliancementioning
confidence: 98%
“…Kepatuhan wajib pajak berarti bahwa wajib pajak akan memenuhi kewajiban perpajakan dan melaksanakan perpajakannya secara sukarela atau kepatuhan berdasarkan paksaan (Darmayasa et al, 2020). Indikator kepatuhan wajib pajak (Dahrani et al, 2021) antara lain; Mendaftarkan diri; Menghitung pajak leh wajib pajak; Membayar pajak; Pelaporan dilakukan wajib pajak.…”
Section: Kepatuhan Wajib Pajakunclassified
“…Berbagai arahan juga telah dikeluarkan oleh Dirjen Pajak agar target penerimaan pemerintah dapat diwujudkan melalui penerimaan pajak. Langkah pemerintah meringankan beban ekonomi pelaku UKM di bidang perpajakan di masa pandemi Covid-19 adalah dengan memberikan insentif pajak yaitu pajak penghasilan (PPh) Final Ditanggung Pemerintah (DTP) (Jayani & Ridhoi, 2021). Melalui PMK Nomor 44/PMK.03/2020 telah diputuskan bahwa insentif pajak final yang semula diberikan untuk UMKM dengan besaran 0.5% kini mendapatkan insentif pajak PPh Final Ditanggung Pemerintah (DTP), maka para pelaku UMKM tidak perlu lagi menyetor dan tidak memotong atau memungut pajak bagi para pelaku UMKM.…”
Section: Pendahuluanunclassified